2018
DOI: 10.1186/s13068-018-1214-9
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic analysis of the camel rumen’s microbiome identifies the major microbes responsible for lignocellulose degradation and fermentation

Abstract: BackgroundThe diverse microbiome present in the rumen of ruminant animals facilitates the digestion of plant-based fiber. In this study, a shotgun metagenomic analysis of the microbes adhering to plant fiber in the camel rumen was undertaken to identify the key species contributing to lignocellulose degradation and short chain volatile fatty acids (VFA) fermentation.ResultsThe density of genes in the metagenome encoding glycoside hydrolases was estimated to be 25 per Mbp of assembled DNA, which is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 70 publications
4
86
1
1
Order By: Relevance
“…Recent studies on the camel gastrointestinal tract metagenome detected at least 27 bacterial phyla. Whereas in the forestomach a higher number of bacteria were associated with amino acid metabolism, replication and repair, carbohydrate metabolism was enriched in the large intestine and faeces (Gharechahi & Salekdeh 2018;He et al 2018). A novel thermo-stable xylanase showing a high activity in a broad pH and temperature range was discovered in the dromedary rumen metagenome, suggesting a potential application in some industrial sectors (e.g.…”
Section: Gut Bacterial Communitiesmentioning
confidence: 99%
“…Recent studies on the camel gastrointestinal tract metagenome detected at least 27 bacterial phyla. Whereas in the forestomach a higher number of bacteria were associated with amino acid metabolism, replication and repair, carbohydrate metabolism was enriched in the large intestine and faeces (Gharechahi & Salekdeh 2018;He et al 2018). A novel thermo-stable xylanase showing a high activity in a broad pH and temperature range was discovered in the dromedary rumen metagenome, suggesting a potential application in some industrial sectors (e.g.…”
Section: Gut Bacterial Communitiesmentioning
confidence: 99%
“…As is well known, the ruminant gastrointestinal microbiota can produce a wide array of CAZymes involved in the utilization of lignocellulosic biomass, which is the most abundant and bio-renewable resource on earth [14,24,25]. In our study, a large repertoire of genes coding for carbohydrate-degrading enzymes were identi ed in the yak fecal microbiome.…”
Section: Diversity Of Carbohydrate-degrading Enzymes and Microbial Comentioning
confidence: 84%
“…Studies demonstrated that members of the Bacteroidetes phylum that contain a varied combination of CAZymes (Carbohydrate-Active Enzymes) in the form of PULs (polysaccharide utilization loci), which encode multiple proteins include the detection, sequestration, hydrolysis and transport of complex carbohydrates (Gharechahi & Salekdeh 2018). It is reported that particular PUL can be used to predict the substrate specificity of microbial strains and the presence of many PULs in Bacteroidetes genomes indicates their broad substrate specifcity and high potential carbohydrate degradation ability (Stewart et PeerJ reviewing PDF | (2018:11:32825:3:0:ACCEPTED 5 Aug 2019)…”
Section: Discussionmentioning
confidence: 99%